Time-Efficient Adjacent Channel Power Ratio Simulation utilizing Overlap-add Signal Decomposition for UMTS Power Amplifiers - Zohny, Amr; Leuschner, Stephan; Kastner, M.; Rascher, Jochen; Ußmüller, Thomas; Müller, Jan-Erik; Fischer, Georg; Weigel, Robert (Asia-Pacific Microwave Conference - APMC 2012, 2012)
The suitability of an RF power amplifier (PA) for modern sophisticated modulation schemes demands high linearity. One of the most significant figures of merit concerning PA linearity is its adjacent channel power ratio (ACPR). The aim of this paper is to propose a time-efficient simulation procedure for ACPR which conforms with the latest 3GPP TS 25.101 specifications for its calculation. This procedure overcomes the time penalty associated with the traditional envelope-based simulation method. The approach is based on standard harmonic balance (HB) tools with MATLAB post-processing incorporating the Overlap-add (OLA) signal decomposition DSP technique for fast RRC filtering. In addition, the simulation results are compared with measurements of a commercial WCDMA PA for verification. Accuracies of better than 0.5dB and 1.1dB are achieved up to 10dB and 2dB backoff respectively.
elib2cris::1512001600,zohny2012b
Keywords: Power Amplifier; Linearity; ACPR; WCDMA; Distortion; Harmonic Balance